Pemanfaatan Teknologi Keuangan sebagai Upaya Peningkatan Mutu Pelaporan Keuangan UMKM - Gusnafitri Gusnafitri (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2023)
Utilization of financial technology as an effort to improve the quality of MSME financial reporting. Current developments in financial technology really help business actors in preparing financial reports per period. This convenience is expected to help business actors in presenting better financial reports. The general objective of this activity is to support MSME (Micro, Small and Medium Enterprises) business actors to improve their ability to record transactions and be able to present financial reports easily so as to produce sustainable financial reports. The method is carried out by making direct visits, conducting observations, conducting questions and answers and providing demonstrations and briefings. The results of this activity provide MSME players with an understanding of how important it is to record financial reports every month. The advantage of making financial reports is that it will make it easier for the owner to control and evaluate his business. Financial technology is an alternative that business actors can use to make it easier to create and present financial reports on an ongoing basis.